The Future of Community Responsibility - Palmer, Geoffrey (Victoria University of Wellington Law Review, 2004)
This paper considers the future of community responsibility – the central philosophical principle of the 1967 Report of the Royal Commission concerning compensation for personal injury in New Zealand (the Woodhouse Report). Central to the Report was the advancement of earnings-related benefits free of all income or means test. Community responsibility was developed by the Royal Commission as the entire basis and principle for its recommendations. This principle has been traced to international instruments like the Universal Declaration of Human Rights. The Australian Woodhouse report proposed a similar version of the principle but the response in the two countries differed. In Australia it was argued that collective responsibility would be the death of individualism whereas in New Zealand the principle was never really attacked and was not seen as alien to the country’s culture. A problem with the notion of community responsibility in both reports is that it is difficult to see how to limit it. In New Zealand the responsibility was restricted to injuries and not extended to sickness, which creates glaring social inequalities and discrimination. However it seems unlikely that this situation will change in the immediate future because of the lack of public disquiet about the issue. In the future, policy in the area may be affected by human rights norms which conflict with the current situation where eligibility for support is based on the manner in which the disability was acquired.